Linking Expression of Fructan Active Enzymes, Cell Wall Invertases and Sucrose Transporters with Fructan Profiles in Growing Taproot of Chicory (Cichorium intybus): Impact of Hormonal and Environmental Cues - Wei, Hongbin; Bausewein, Anja; Steininger, Heike; Su, Tao; Zhao, Hongbo; Harms, Karsten; Greiner, Steffen; Rausch, Thomas (Frontiers in Plant Science, 2016)
In chicory taproot, the inulin-type fructans serve as carbohydrate reserve. Inulin metabolism is mediated by fructan active enzymes (FAZYs): sucrose:sucrose 1-fructosyltransferase (1-SST; fructan synthesis), fructan:fructan-1-fructosyltransferase (1-FFT; fructan synthesis and degradation), and fructan 1-exohydrolases (1-FEH1/2a/2b; fructan degradation). In developing taproot, fructan synthesis is affected by source-to-sink sucrose transport and sink unloading. In the present study, expression of FAZYs, sucrose transporter and CWI isoforms, vacuolar invertase and sucrose synthase was determined in leaf blade, petiole and taproot of young chicory plants (taproot diameter: 2cm) and compared with taproot fructan profiles for the following scenarios: i) N-starvation, ii) abscisic acid (ABA) treatment, iii) ethylene treatment (via 1-aminoyclopropane-1-carboxylic acid [ACC]), and iv) cold treatment. Both N-starvation and ABA treatment induced an increase in taproot oligofructans. However, while under N-starvation this increase reflected de novo synthesis, under ABA treatment gene expression profiles indicated a role for both de novo synthesis and degradation of long-chain fructans. Conversely, under ACC and cold treatment oligofructans slightly decreased, correlating with reduced expression of 1-SST and 1-FFT and increased expression of FEHs and VI. Distinct SUT and CWI expression profiles were observed, indicating a functional alignment of SUT and CWI expression with taproot fructan metabolism under different source-sink scenarios.